Dampak Pandemi COVID-19 pada Usaha Kerajinan Aceh Souvenir Kupula Indah di Kabupaten Pidie - Fadli Syahputra; Muhammad Zainal Abidin; Kamal Fachrurrozi; Sry Rasyiidu Tebe; Sarfia Fonna (Jurnal Penelitian Ekonomi Akuntansi, 2022)
This research was conducted with the aim of knowing the impact of the Covid-19 pandemic on the Aceh Kupula Indah souvenir craft business in Garot Kab. Pidie. Data collection was carried out using interviews and questionnaires to the owner of the Kupula Indah Souvenir business and the head of the District UMKM Office. Pidie. This research method is descriptive qualitative analysis. The results showed that the Covid-19 pandemic had a bad impact on the sustainability of the Kupula Indah Souvenir craft business. Sales turnover decreased by 52% during the pandemic. The level of business productivity has become more passive during the spread of the Covid-19 pandemic. There are many obstacles in the marketing of souvenir products and the difficulty of achieving sales targets due to the continued spread of Covid-19, resulting in the government issuing a policy of limiting all public activities, which also hampers economic activities. It is hoped that the Kupula Indah Souvenir business owner should upgrade and develop new strategies in the Kupula Indah Souvenir business marketing system so that it can continue to grow and survive in the midst of the Covid-19 pandemic, and the MSME Service is expected to be more optimal in conducting coaching activities for business owners. and carried out evenly even though in a short time but also adequately